The Genesis and Development of Church Legislation on Education in the Middle Ages - Ratajczak, Krzysztof (Biuletyn Historii Wychowania, 2018)
This paper is to present the beginnings and the subsequent development and evolution of church law in the sphere of education from the 4th to the beginning of the 16th century. The roots of the acts of law presented by the Popes, synods and councils were based on the traditions of Roman law, but a variety of reasons from the field of policy, economy and society led to the need to establish a church school system. The aim of the Church was to create an independent school system with its own purposes, different from secular schools.